The information society progress: evolution of the Health Information Services - Pestana, Olívia (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
The health sector is an area where information society effects are being clearly visible: new technologies applied to several procedures, no barriers in communication worldwide, faster access to research and scientific information are some examples of a scenario that from now on will be irreversibly close to informational changes. Information services also reflect the effects of the information society, whether in the renewal of their powers, whether in new demands for information professionals. Taking the new paradigm of information science as the theoretical-epistemological reference of this work, the author presents the effects of the paradigmatic transition in the sector of the Health Information Services, using as interpretation framework the Frank Webster’s information society approaches: technological, economic, occupational, spatial and cultural.